2020
DOI: 10.1021/acscentsci.0c00763
|View full text |Cite
|
Sign up to set email alerts
|

Kidney-Targeted Cytosolic Delivery of siRNA Using a Small-Sized Mirror DNA Tetrahedron for Enhanced Potency

Abstract: A proper intracellular delivery method with target tissue specificity is critical to utilize the full potential of therapeutic molecules including siRNAs while minimizing their side effects. Herein, we prepare four small-sized DNA tetrahedrons (sTds) by self-assembly of different sugar backbone-modified oligonucleotides and screened them to develop a platform for kidney-targeted cytosolic delivery of siRNA. An in vivo biodistribution study revealed the kidney-specific accumulation of mir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 37 publications
0
54
0
Order By: Relevance
“…Hence, TDNs are a promising nucleic acid carrier for gene delivery. [26][27][28] Previous studies have shown that TDNs can significantly promote the locomotion, regulation, and proliferation of chondrocytes. [31] Moreover, TDNs have been proven to be crucial regulators of the increase in osteogenic potential and adipose-derived stem cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, TDNs are a promising nucleic acid carrier for gene delivery. [26][27][28] Previous studies have shown that TDNs can significantly promote the locomotion, regulation, and proliferation of chondrocytes. [31] Moreover, TDNs have been proven to be crucial regulators of the increase in osteogenic potential and adipose-derived stem cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…SELEX of functional L ‐nucleic acids has demonstrated outstanding potential in development of L ‐aptamer to specifically bind different molecular targets, [16–17] and even creation of a mirror‐image polymerization system [18–19] . Besides, L ‐nucleic acid has also been applied to construct unique DNA nanostructure as advanced material and drug delivery device, [20] and the unique features of L ‐nanostructure could offer the superior stability to ensure the effective biodistribution in vivo [21] …”
Section: Methodsmentioning
confidence: 99%
“…[18][19] Besides, L-nucleic acid has also been applied to construct unique DNA nanostructure as advanced material and drug delivery device, [20] and the unique features of L-nanostructure could offer the superior stability to ensure the effective biodistribution in vivo. [21] Considering the practical value of fluoro-modification in nucleic acid-related research fields, and the exceptional potential of L-nucleic acids as next-generation of molecular therapy, it is critical to further explore the fluorinated L-DNA/L-RNA to expand their biomedical applications. The fluorineinduced pseudo-hydrogen bonds and sugar conformational change are possible to engender the unique ligand-binding aptamers.…”
mentioning
confidence: 99%
“…A very interesting property of DNA nanostructures is that they have been reported to not accumulate in the liver [ 4 , 130 ]. In fact, in vivo biodistribution of a small-sized DNA tetrahedron favored kidney-specific accumulation after intravenous administration in a mouse model [ 27 ]. The authors indicated that low opsonization with serum proteins reduced liver clearance and the small size of the nanostructure allowed it to pass though the glomerular filter and be endocytosed by tubular cells.…”
Section: Overcoming Delivery Problemsmentioning
confidence: 99%
“…The authors indicated that low opsonization with serum proteins reduced liver clearance and the small size of the nanostructure allowed it to pass though the glomerular filter and be endocytosed by tubular cells. Importantly, the authors have demonstrated the functionality of this platform by achieving intracellular delivery of p53 siRNA and improved markers of AKI in mice [ 27 ].…”
Section: Overcoming Delivery Problemsmentioning
confidence: 99%